Middle ear anatomy and implant sizes: correlates and the need for uniform implant dimensions - Lenarz, Thomas; Becker, Moritz; Warnecke, Athanasia; Giesemann, Anja; Prenzler, Nils Kristian; Steinhardt, Uwe; Schurzig, Daniel (Frontiers in Audiology and Otology, 2024)
Introduction Conductive hearing loss describes an insufficient sound transfer of the middle ear, often caused by defects or absence of the ossicles. Depending on the specific middle ear dimensions and the kind of defect, surgeons can choose from a variety of passive implants to reconstruct the middle ear and hence restore sound transmission. However, the latter is only achieved if the optimal implant size is available and selected for each individual patient. Methods Anatomical dimensions relevant for middle ear reconstruction were assessed within high-resolution clinical imaging data of 50 patients (100 ears). The ranges of these dimensions were then compared to implant types and sizes available from different manufacturers. Results In general, total and partial prostheses seem to cover the whole range of anatomical variations. A lack of stapesplasty implants was found for particularly small anatomies. Various implant lengths of all types far exceed dimensions necessary for successful restoration of sound transmission. In some cases, implant lengths are not clearly specified by the manufacturer. Tympanic membrane and stapes axis were not in line for any of the investigated middle ears. Conclusion Clear specifications of implant lengths are crucial to allow for successful hearing restoration, and clinics often need to have more than one implant type to cover the entire range of anatomical variations they may encounter. There appears to be an unmet clinical need for smaller stapesplasty implants. Devices which allow for an angular adjustment between distal and proximal end appear to mimic the orientation of the ossicles more naturally.